Fiscal Equalization Schemes and Fiscal Sustainability - Niklas Potrafke; Markus Reischmann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Fiscal sustainability tests have largely ignored the institutional setting of fiscal policy making. Fiscal equalization schemes in federal states are one such institution. We examinewhether German state governments pursue sustainable fiscal policies taking intoaccount fiscal equalization transfers. Using panel data techniques we assess fiscal sustainability by investigating whether the debt-to-GDP-ratio has had a positive influence on the primary surplus (Bohn-model). Distinguishing between different measures of theprimary surplus we show that including/excluding fiscal transfers changes the results of the Bohn-model. While fiscal equalization transfers do render the fiscal policy of the states sustainable they also provide the states with incentives to increase government spending which, eventually, might render the entire equalization scheme politically unsustainable.
Keywords: H77; H72; H62; C23; 330; Fiscal sustainability; institutions; fiscal equalization schemes; panel data; Finanzausgleich; Länderfinanzen; Nachhaltigkeit; Deutschland